DESIGN OF PROPORTIONAL INTEGRAL DERIVATIVE (PID) CONTROLLER FOR BUS SUSPENSION SYSTEM USING MATLAB SOFTWARE - IQBAL, MUHAMMAD (2011)
The research is presented as a development of an active suspension system for quarter-car model to improve the system's performance of car by applying a Proportional Integral Derivative (PID) controller. The method used to achieve the goal of this research is by using computer simulation in Matlab. The research is started by modeling bus suspension system as a quarter model in a free body diagram to get the equations of motion. Then, this equations of motion is transformed into state space and transfer function model to get the loop control. After getting the open loop and the closed loop system, the design of PID controller is done. The controller design deals with the selection of proportional, integral, and derivative gain parameters ( , , and ). The results from simulation show that by applying PID controller to the suspension system, performance of the system has been improved. It reduced the settling time of natural response from 33.5 seconds to less than 5 seconds. The peak amplitude and the rise time have been also improved, which are from 2.25x10-5 m and 0.24 seconds becoming -8.8x10-3 m, and 0.13 seconds, respectively. Further, the steady state error is 3.35x10-6 m which indicates that the system has satisfied the passenger comfort.